Lyme Carditis Complicated by Polymorphic Ventricular Tachycardia and Cardiac Arrest: A Case Report - Negar Esfandiari BHSc; Tanesha Beebe-Peat MD; Anna Quinlan BA; Beth Wagner DO; Tyler Wark MD; Robert Lobel MD (Journal of Investigative Medicine High Impact Case Reports, 2022)
Lyme disease is commonly encountered in endemic areas of the United States harboring the causal organism Borrelia burgdorferi . Lyme carditis can manifest in early disseminated infections, usually as atrioventricular nodal blockade. Timely antibiotic therapy typically suppresses myocardial inflammation and reverses cardiac conduction disturbances. We present a case of a previously healthy male who presented to the emergency department with non-prodromal syncope, multifocal annular rashes, and antecedent inflammatory knee pain and effusion, found to have positive 2-tier Lyme testing and pause-dependent polymorphic ventricular tachycardia leading to cardiac arrest. Lyme carditis occurs in early disseminated infections but rarely leads to cardiac arrest. Acute management is entrained in well-established guidelines for therapy, and together with risk stratification scoring can be considered by emergency care physicians in the workup of undifferentiated syncope with concern for Lyme disease with cardiac involvement.